2018
DOI: 10.1111/jcmm.14041
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Krüppel‐like factor 2 reduces K/BxN serum‐induced arthritis

Abstract: Krüppel‐like factor 2 (KLF2) critically regulates activation and function of monocyte, which plays important pathogenic role in progressive joint destruction in rheumatoid arthritis (RA). It is yet to be established the molecular basis of KLF2‐mediated regulation of monocytes in RA pathogenesis. Herein, we show that a class of compound, HDAC inhibitors (HDACi) induced KLF2 expression in monocytes both in vitro and in vivo. KLF2 level was also elevated in tissues, such as bone marrow, spleen and thymus in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Specifically in mice, induction of KLF2 in immune cells reduced arthritic inflammation and attenuated joint destruction. Furthermore, coimmunoprecipitation confirmed the direct interaction between KLF2 and HDAC4, thereby providing the groundwork to understand the molecular mechanisms whereby KLF2 regulates RA pathogenesis (80). Altogether, these data demonstrate a novel protective role of KLF2 in regulation of RA severity and progression.…”
Section: Emerging Roles Of Klf2 In Bone Metabolismmentioning
confidence: 53%
See 2 more Smart Citations
“…Specifically in mice, induction of KLF2 in immune cells reduced arthritic inflammation and attenuated joint destruction. Furthermore, coimmunoprecipitation confirmed the direct interaction between KLF2 and HDAC4, thereby providing the groundwork to understand the molecular mechanisms whereby KLF2 regulates RA pathogenesis (80). Altogether, these data demonstrate a novel protective role of KLF2 in regulation of RA severity and progression.…”
Section: Emerging Roles Of Klf2 In Bone Metabolismmentioning
confidence: 53%
“…Together, the data indicate that KLF2 plays an important role in attenuating inflammation and inhibiting osteoclastogenic differentiation and function in RA. ; data from our lab show that KLF2 knockdown significantly increased enrichment of the active histone marks H3K9Ac and H4K8Ac and respective histone acetylase transfer (HAT) enzymes P300 and PCAF at the enrichment sites for the MMP9 gene (80). KLF2 inhibits pro-inflammatory markers, thereby further inhibiting monocytic activation (72).…”
Section: Emerging Roles Of Klf2 In Bone Metabolismmentioning
confidence: 91%
See 1 more Smart Citation
“…KLF2 is one of the important members of the KLF family, which was first identified as a critical regulator for normal lung development [ 27 ]. Later it was revealed that it has implications in many important biological processes, such as T cell migration [ 28 ], embryonic erythropoiesis [ 29 ], vascular integrity [ 30 ], and monocyte activation, function, and differentiation [ 11 , [31] , [32] , [33] , [34] ]. Studies suggest that KLF2 is essential for maintaining ground state pluripotency of mouse embryonic stem cells [ 35 ], differentiation of endothelial progenitor cells to endothelial cells induced by shear stress [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor Krüppel-like factor 2 (KLF2) plays an important role in the regulation of a variety of immune cells, including proinflammatory activation and function of monocytes [18,19,20,21], and myeloid cell polarization [22]. KLF2, also known as lung KLF, as it was first found in the adult mouse lung [23], plays a major regulatory role in hematopoietic cell biology, including cell quiescence, cell proliferation, differentiation, and survival [24].…”
Section: Introductionmentioning
confidence: 99%